Talk test : a simple alternative to identify lactate thresholds during progressive cycling exercise - De Lucca, Leonardo (Array, 2021)
The assessment of speech production difficulty has been used to control aerobic exercise intensity through the Talk Test method. The aim of this study was to compare the Talk Test variables to lactate thresholds using an incremental test. Thirteen male subjects performed an incremental cycle test to identify the first lactate threshold (LT1), second lactate threshold (LT2) and transition points of the Talk Test. During the incremental exercise test subjects read aloud a standard paragraph at the end of each stage. The last stage at which the subjects could talk comfortably, the first stage at which the subjects could not talk comfortably, and the first stage at which they definitely could not talk comfortably were referred to as the last positive (LP), equivocal (EQ) and negative stages (NEG), respectively.